2006
DOI: 10.1002/jmv.20681
|View full text |Cite
|
Sign up to set email alerts
|

Identification of viral agents causing diarrhea among children in the Eastern Center of Tunisia

Abstract: Viral diarrhea remains a major cause of childhood morbidity and mortality worldwide. In Tunisia, no comprehensive studies of all viral agents related to diarrhea in children have yet been conducted. The present study was performed to investigate the role of enteric viruses in acute diarrhea in the country. Six hundred thirty-eight stool samples were collected from children under 5 years of age seeking medical care for acute diarrhea between October 2003 and September 2005 in hospitals from the Eastern-Center T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
38
3
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 33 publications
6
38
3
1
Order By: Relevance
“…The positive singlestranded RNA (ssRNA) family Astroviridae consists of two genera, Avastrovirus and Mamastrovirus, known to infect avian and mammalian hosts, respectively. Human astroviruses are transmitted through the fecal-oral route and have been associated with gastroenteritis (13,26,29,32,39,91). Several new human astroviruses have recently been described (24,25,44).…”
Section: Figmentioning
confidence: 99%
“…The positive singlestranded RNA (ssRNA) family Astroviridae consists of two genera, Avastrovirus and Mamastrovirus, known to infect avian and mammalian hosts, respectively. Human astroviruses are transmitted through the fecal-oral route and have been associated with gastroenteritis (13,26,29,32,39,91). Several new human astroviruses have recently been described (24,25,44).…”
Section: Figmentioning
confidence: 99%
“…In Tunisia, a middle-income Mediterranean country, earlier studies showed the contribution of RVs (8,38) and more recently that of HAstVs and HAdVs (12) in cases of childhood diarrhea. However, the nature of the contribution of NoVs and Aichi viruses to outbreaks of gastroenteritis in Tunisia remains unknown.…”
mentioning
confidence: 99%
“…The G12 rotavirus was first detected in 1990 in the Philippines (35) and has since been found in Asia, Europe, South America, and North America, suggesting that it is possibly emerging all over the world (5,6,18,28,29,32). So far, no cases concerning the G12 rotavirus strain have been reported in northern Africa (11,31).…”
mentioning
confidence: 99%
“…To date, there have been few epidemiological surveys that aimed to determine the circulation of enteric viruses in Egypt and other countries in the Middle East (11,31,36). The aim of this work was to determine the circulation of enteric viruses among the population of Cairo, Egypt.…”
mentioning
confidence: 99%